Oral Health Birth Cohort Studies: Achievements, Challenges, and Potential. (November 2020) - Peres, K.G.; Thomson, W.M.; Chaffee, B.W.; Peres, M.A.; Birungi, N.; Do, L.G.; Feldens, C.A.; Fontana, M.; Marshall, T.A.; Pitiphat, W.; Seow, W.K.; Wagner, Y.; et al.
Birth cohorts are those among observational studies that provide understanding of the natural history and causality of diseases since early in life. Discussions during an International Association for Dental Research symposium in London, United Kingdom, in 2018, followed by a workshop in Bangkok, Thailand, in 2019, concluded that there are few birth cohort studies that consider oral health and that a broader discussion on similarities and differences among those studies would be valuable. This article aims to 1) bring together available long-term data of oral health birth cohort studies from the low, middle, and high-income countries worldwide and 2) describe similarities and differences among these studies. This work comprises 15 studies from all 5 continents. The most studied dental conditions and exposures are identified; findings are summarized; and methodological differences and similarities among studies are presented. Methodological strengths and weaknesses are also highlighted. Findings are summarized in 1) the negative impact of detrimental socioeconomic status on oral health changes over time, 2) the role of unfavorable patterns of dental visiting on oral health, 3) associations between general and oral health, 4) nutritional and dietary effects on oral health, and 5) intergenerational influences on oral health. Dental caries and dental visiting patterns have been recorded in all studies. Sources of fluoride exposure have been documented in most of the more recent studies. Despite some methodological differences in the way that the exposures and outcomes were measured, some findings are consistent. Predictive models have been used with caries risk tools, periodontitis occurrence, and permanent dentition orthodontic treatment need. The next steps of the group's work are as follows: 1) establishing a consortium of oral health birth cohort studies, 2) conducting a scoping review, 3) exploring opportunities for pooled data analyses to answer pressing research questions, and 4) promoting and enabling the development of the next generation of oral health researchers.